The Gambia : First Review Under the Extended Credit Facility, Request for Nonobservance of Performance Criterion, and Request for Rephasing of Reviews. (IMF Staff Country Reports; Country Report ;, 2013)
The Gambian economy is still recovering from the severe drought and crop failure. Depreciation pressure on the Dalasi has largely been driven by weaknesses in the balance of payments and uncertainty about exchange rate policy. Executive Directors have urged the government to curb domestic borrowing and to sustain the fiscal adjustment needed to reduce the high cost and risks of domestic debt. They have also commended the progress achieved toward eliminating fiscal dominance and encourage implementing a restrained monetary policy.